SPORADIC INCREASE OF PARTICLE SEDIMENTATION AT THE ICE EDGE OF THE ANTARCTIC OCEAN DURING THE AUSTRAL SUMMER 1994-1995 (18th Symposium on Polar Biology) - ササキ, ヒロシ; スズキ, ヒデカツ; タカヤマ, マコト; スズキ, コウジ; ハンダ, ノブヒコ; クドウ, サカエ; フクチ, ミツオ; SASAKI, Hiroshi; SUZUKI, Hidekatsu; TAKAYAMA, Makoto; SUZUKI, Koji; HANDA, Nobuhiko; et al. (National Institute of Polar Research, 1997)
P(論文) Time-series sediment traps were deployed at depths of 537 m, 796 m, 1259 m, 1722 m and 2727 m at ice edge of the Antarctic Ocean (64°42'S, 139°58'E) from 26 December 1994 to 20 January 1995. During a short period from 7 to 9 January, a sporadic flux increase within a few days in terms of total dry weight of 774 mg m^<-2>d^<-1> at 537 m was observed. The mass of sinking particles forming the flux maximum sank down to the deepest trap (2727 m) within 7-11 days, indicating that about 5% of these particles were transported downward to the bottom with the sinking rate of 199-313 m d^<-1> (mean 243 m d^<-1>). The considerable particle loss rate (13% [100 m]^<-1>) below the mesopelagic layers in a short period suggests the occurrence of consumption processes induced by the sporadic supply of freshly produced particles from above. departmental bulletin paper